Keeping It Fake: Exploring User-Generated Political Fakes and Their Publics - Ferrari, Elisabetta (AoIR Selected Papers of Internet Research, 2016)
This paper investigates user-generated political satire, focusing in particular on one genre: fake political accounts. Such fakes, created as social network profiles, satirize politicians or political organizations by impersonating them. Through semi-structured interviews with a sample of Italian fake accounts creators, I explore how the fakes navigate their fakeness vis-à-vis the affordances of social network sites and their public(s). I identify two modes of faking: mimetic and explicit. I map the interactions of the fakes and their public(s) along two axes: one referring to the public’s understanding of the satire, the other to the uses that the public makes of the satire. Thirdly, I argue for fakeness as a playful, yet powerful critique of the political and its pretense to authenticity. By focusing on how the creators of fake accounts manage their fakeness and interact with their public(s), this paper provides insights on the participatory nature of satire and on the characteristics of online publics.